The challenge of paradigm shift in formulating formal legality principles into formal and material principles in the revision of the criminal code - Wahyuning Kiscahyani (Universitas Negeri Yogyakarta, 2025)
This research aims to examine the challenges of shifting the paradigm of the formulation of formal legality principles to formal and material in the reform of the Criminal Code which is still an academic debate by criminal law experts. Regarding this paradigm shift, some criminal law experts consider the change to be a form of expansion of the principle of legality, but others consider it as a setback. The method used is a normative or doctrinal legal method with a legislative and conceptual approach. Meanwhile, the data used is secondary data or literature data in the form of primary legal materials and secondary legal materials. This research found that the paradigm shift in the formulation of the principles of formal legality to formal and material in the provisions of Law Number 1 of 2023 regarding the Criminal Code is appropriate because it is a form of effort by the Indonesian nation to reorient and reform the criminal law in accordance with the socio-cultural values of the Indonesian people. Then to the challenges that will arise in the future regarding the complexity of cases that are closely related to the implementation of the principle of material legality in the new Criminal Code, each region can immediately codify the unwritten laws that are alive and applicable in its society into the form of Regional Regulations.